Transcriptomic insights into mycorrhizal interactions with tomato root: a comparative study of short- and long-term post-inoculation responses - Abdelsattar, Mohamed; Soliman, Maali S.; Mohamed, Rasha A.; Radwan, Khaled H.; El-Mahdy, Mohamed M.; Mousa, Khaled H.; Khalil, Shaimaa R. M.; Osman, Engy; Alameldin, Hussien F.; Hussein, Ahmed; Hassanein, Sameh E.; Abdallah, Naglaa A.; et al. (Frontiers in Genetics, 2024)
The symbiosis of arbuscular mycorrhizal (AM) is a beneficial association between plant roots and fungi that enhances the uptake of mineral nutrients from the soil and enables the plant to tolerate abiotic and biotic stresses. Although previous RNA-seq analyses have identified a large number of AM-responsive genes in model plants such as Solanum lycopersicum L., further studies are ongoing to comprehensively understand the complex interaction between plants and AM in roots, especially in short-and long-term responses after inoculation. Here, we used RNA-seq technology to obtain the transcriptome of roots inoculated with the fungus Rhizophagus irregularis at 7 and 30 days post inoculation (dpi). Of the 1,019 deferentially expressed genes (DEGs) in tomato roots, 635 genes showed differential expression between the mycorrhizal and non-mycorrhizal associations at the two different time points. The number of upregulated DEGs far exceeded the number of downregulated ones at 7 dpi and this difference decreased at 30 dpi. Several notable genes were particularly involved in plant defense, plant growth and development, ion transport and biological processes, including GABAT, AGP, POD, NQO1, MT4, MTA and AROGP3. In addition, KEGG pathway enrichment analysis revealed that some of the genes are involved in different pathways, including ascorbic acid (AFRR, GME1 and APX), metabolism (CYP, GAPC2 and CAM2) and sterolipids (CYC1 and HMGR), as well as genes related to cell division and cell cycle (cdkB2 and PCNA). These results provide valuable new data on AM-responsive genes in tomato roots at both the short-1 Abdelsattar et al.and long-term post-inoculation stages and contribute to deciphering the biological processes that occur between tomato roots and symbiotic fungi.